Metallography of Iron alloys containing Phosphorus - Mohammed Misbahul, Amin; Upadhyaya, Gopal Shankar (Carl Hanser Verlag, 2009)
Link to publisher's homepage at http://www.materialography.de/PractMet/Archive/2008/index.php?id=g